An Exhaustive Epistatic SNP Association Analysis on Expanded Wellcome Trust Data - Lippert, Christoph; Listgarten, Jennifer; Davidson, Bob; Baxter, Jeff; Poon, Hoifung; Kadie, Carl; Heckerman, David (Scientific Reports, 2013)
We present an approach for genome-wide association analysis with improved power on the Wellcome Trust data consisting of seven common phenotypes and shared controls. We achieved improved power by expanding the control set to include other disease cohorts, multiple races, and closely related individuals. Within this setting, we conducted exhaustive univariate and epistatic interaction association analyses. Use of the expanded control set identified more known associations with Crohn's disease and potential new biology, including several plausible epistatic interactions in several diseases. Our work suggests that carefully combining data from large repositories could reveal many new biological insights through increased power. As a community resource, all results have been made available through an interactive web server.